Chemical Constituents with Anti‐allergic Activity from the Barks of Cinnamomum cambodianum Collected in Cambodia. (January 2015) - Pel, Pisey; Kim, Young‐Mi; Chin, Young‐Won
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10022-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>